INFLUENCE OF COW MANURE IN PLANTING MEDIA AGAINST THE GROWTH OF BANANA CORM OF BANANA KEPOK (Musa paradisiaca L.) - Renfiyeni - Renfiyeni; Helti Andraini; Friza Elinda (JERAMI : Indonesian Journal of Crop Science, 2022)
This study aims to obtain the composition of soil and cow dung that provides the best growth for kepok banana seedlings using banana corm.. This research was conducted in Sijunjung Regency. Efforts to provide banana seeds are carried out by utilizing banana corm which will produce 3 and 4 tillers per tuber and the production time is much faster than seeds from tillers. To get the best banana corm growth, a study was conducted using a mixed planting medium of soil and cow manure with five comparisons. The treatments were: A. Soil with cow manure 1:1 ratio, B. Soil with cow manure 2:1 ratio, C. Soil with cow manure 3:1 ratio, D. Soil with cow manure 4:1 ratio, E .Soil only. The treatment was repeated 5 times. The design used was a randomized block design and continued with DNMRT (Duncan New Multiple Range Test). Parameters observed were when shoots appeared, percentage of growth, shoot height, stem diameter, number of leaves, leaf length, root length and number of roots. The results showed that the best planting medium for planting banana kepok from corm was a medium consisting of soil and cow manure with a ratio of 1:1. This treatment gives the best results for all parameters.